Kontribusi Pesantren Dalam Merespon Dinamika Sosial Keagamaan - Muhaemin Muhaemin (Institut Agama Islam Negeri Palopo, 2019)
This study aims to analyze and map the role of pesantren in social aspects and religious development in its relevance to local culture and global dynamics. The study design used a qualitative approach with a number of selected informants. The research location was in the Nurul Junaidiyah Lauwo Luwu Timur Islamic boarding school which was one of the pesantren that developed in the Tana Luwu area of South Sulawesi. The results of the study showed that the Islamic Boarding School Nurul Junaidiyah had carried out a role in the social field, namely holding formal education, accommodating santri from poor families, organizing economic empowerment activities through cooperatives. In the aspect of religious development, the Pesantren Junaidiyah Lauwo became a pioneer of moderate Islamic da'wah involving Kyai, Caregivers, Teachers, santri and alumni. Along with the global dynamics, it is necessary to increase the role of pesantren through cooperation with alumni ties, government, and other institutions. In the aspect of religious development, the Nurul Junaidiyah Islamic Boarding School has made good contributions, especially in printing the memorization of the Koran, but the social aspects need to improve social programs such as fostering orphans, fostering converts and or establishing ulema cadre centers (ma'had aly).